Bilateral clavicle fractures of the medial third treated by inverted anatomic locking plates: a case report - Tong, Jian; Zhang, Ming; Yu, Qing (Frontiers in Surgery, 2025)
Bilateral medial third clavicle fractures are very rare, with only very few cases reported in the literature. The mechanism underlying this type of fracture is often complex, and so far, its treatment remains controversial. We report a case of bilateral medial third clavicle fractures after a traffic accident. X-ray showed dislocation of bilateral medial third clavicles. The patient was cured by surgery and instrument fixation. Both clavicles were fixed using an inverted anatomic locking plate. The patient had excellent shoulder function after 2 years of surgery. Clavicle stability is necessary for normal shoulder function, and surgical fixation is becoming a trend for displaced medial third clavicle fractures. In this study, we reported a patient with bilateral clavicle fractures of the medial third who was treated by surgery and achieved excellent shoulder movement. An inverted anatomic locking plate is an effective internal fixation material for treating this type of fracture.